Graphdiyne‐Based Monolayers as Promising Anchoring Materials for Lithium–Sulfur Batteries: A Theoretical Study. Issue 3 (21st January 2020) - Muhammad, Imran; Younis, Umer; Xie, Huanhuan; Kawazoe, Yoshiyuki; Sun, Qiang
Abstract: High energy density, low cost, and environmental friendliness are required for modern energy‐storage technologies. The anchoring performance of newly fabricated porous triphenylene–graphdiyne (TPGDY), boron–graphdiyne (BGDY), and nitrogen–graphdiyne (NDGY–C18N6, NGDY–C24N4, and NGDY–C36N6) monolayers are studied by employing density functional theory (DFT). It is found that the porous graphdiyne‐based materials offer more space to accommodate lithium polysulfides with moderate adsorption energies and the anchoring performance changes with substrate and the size of Li2S n molecules: BGDY has a strong chemical interaction with lithium polysulfides due to the large charge transfer as compared to others. The chemical interaction dominates in anchoring species Li2S n with small size ( n = 1, 2), whereas vdW interaction dominates for S 8 and larger size Li2S n ( n = 6, 8) species. Furthermore, anchoring lithium polysulfides reduces the band gaps of the graphdiyne‐based materials and enhances the electronic conductivity. These intriguing features suggest that graphdiyne‐based porous 2D structures are promising anchoring materials for lithium–sulfur batteries. Abstract : Each material shows a distinct adsorption behavior with Li2 S n clusters, while the strength of adsorption energy is related to the amount of charge transfer and distance of the cluster from substrate. BGDY, TPGDY, NGDY–C18 N6, and NGDY–C36 N6, substrates exhibit moderate adsorption energies for Li2 S n molecules, which can avoid the dissolution into electrolyte.